Analisis tentang Minat Bermain Bolavoli Kelas 7-8 Putra pada Ekstrakurikuler di SMP Negeri 5 Surabaya - Denny Febriansyah; Andun Sudijandoko; Lutfhi Abdil Khuddus; Hijrin Fithroni (Atletik Karya: Jurnal Pendidikan dan Olahraga Aktual, 2025)
This study aims to analyze the level of interest of male students in grades 7-8 in Volleyball Extracurricular activities at SMP Negeri 5 Surabaya. The background of this study is based on the fact that the majority of male students prefer other Extracurricular activities compared to Volleyball, even though SMP Negeri 5 Surabaya has a dynamic Extracurricular program. Analysis of student interest in this activity is still rarely done, so this study focuses on the interest of male students in grades 7-8 in participating in Volleyball Extracurricular. The type of quantitative descriptive research with a questionnaire method. The population in this study were students who actively participated in Volleyball Extracurricular activities totaling 22 students, with the sampling technique used was purposive sampling with a quota approach. The researcher set a quota of 13 respondents / 13 male students in grades 7-8 who came from members of the Volleyball Extracurricular at SMP Negeri 5 Surabaya. The results of the study showed interest in Extracurricular activities among male students in grades 7-8 at SMP Negeri 5 Surabaya, the majority of male students were included in the high category of 38.46%. It is concluded that the interest of male students who participate in the Volleyball Extracurricular at SMP Negeri 5 Surabaya is in the high category.